Penerapan Metode Karya Wisata Dalam Meningkatkan Kemampuan Bercerita Anak Di Taman Kanak Kanak - Syafiqoh, Imro'atus (Institut Agama Islam Tarbiyatut Tholabah, 2024)
This case study research aims to determine the application of the field trip method in improving children's storytelling abilities at Muslimat 05 Kindergarten. Data collection techniques use observation and interviews with school principals and teachers. Data were analyzed qualitatively with stages of data cleaning, transcription, coding and categorization, and interpretation. The results of this research are that the application of the field trip method can improve children's speaking skills and increase children's confidence in telling stories. Children often tell stories about several vehicles they encountered during field trips as well as about captains, machinists, pilots and drivers who had time to ask and answer questions with the children. Even though this activity has problems related to financing, the response from the parents of students who took part in this activity were all satisfied and happy because their children looked quite active and happy when talking about the field trip activities they carried out